Adult-Onset Leukoencephalopathy with Axonal Spheroids and Pigmented Glia: An MRI Study of 16 French Cases - Codjia, P.; Ayrignac, X.; Mochel, F.; Mouzat, K.; Carra-Dalliere, C.; Castelnovo, G.; Ellie, E.; Etcharry-Bouyx, F.; Verny, C.; Belliard, S.; Hannequin, D.; Marelli, C.; et al. (American Journal of Neuroradiology, 2018)
SUMMARY: Adult-onset leukoencephalopathy with axonal spheroids and pigmented glia is an autosomal dominant leukoencephalopathy related to CSF1R gene mutations. A growing number of clinicoradiologic phenotypes have been described. In this study, we analyzed brain imaging findings in 16 patients with adult-onset leukoencephalopathy with axonal spheroids and pigmented glia to refine radiologic diagnostic clues. T2/FLAIR white matter hyperintensities were present in all patients with frontal or frontoparietal predilection, with asymmetric distribution in more than one-third. Brain atrophy and callosal involvement were almost constant, and corticospinal tract involvement was frequent. Moreover, deep white matter hyperintense dots on DWI and deep punctate calcifications on CT were often found. Conversely, deep gray matter nuclei, external capsules, and brain stem were rarely involved. Our series emphasized the great variability of MR imaging findings seen in adult-onset leukoencephalopathy with axonal spheroids and pigmented glia. A complete imaging screening including DWI, T2*, and CT is mandatory to accurately assess patients with suspected inherited adult-onset leukoencephalopathy.ALSPadult-onset leukoencephalopathy with axonal spheroids and pigmented gliaFTLDfrontotemporal lobar degenerationWMHwhite matter hyperintensities